India's COVID-19 social assistance package and its impact on the agriculture sector - Varshney, Deepak; Kumar, Anjani; Mishra, Ashok K.; Rashid, Shahidur; Joshi, Pramod Kumar (Elsevier, 2021)
COVID-19 induced significant economic and social disruptions in India. Rural households, including smallholders, were affected by loss in migrant income, livelihood and farm and non-farm incomes. During this lockdown, the Indian government enacted several emergency legislations to provide direct and indirect relief to workers and households. India's COVID-19 social assistance package, namely, PM-GKY, announced in March 2020, was designed to provide immediate relief to the vulnerable population. The PM-GKY provided cash direct benefit transfers (DBT) and in-kind supports (IKS) through existing schemes.